Electrical Properties Inorganic-on-Organic Hybrid GaAs/Graphene Oxide Schottky Barrier Diode - Kirsoy, A.; Ahmetoglu, M.; Okutan, M.; Yakuphanoglu, F. (AMER SCIENTIFIC PUBLISHERS, 2016)
The Au88Ge12 alloy/n-type GaAs(100)/Graphene Oxide (GO)/Au Schottky barrier diode has been fabricated. GO has been prepared by Hummers method and deposited on the GaAs substrate by spraying method. Schottky diode was investigated under dark and light intensity by the current-voltage (I-V) characteristics of the heterojunction. Thermionic current mechanism above the barrier has been detected by current-voltage measurements. It was found that the barrier height increases and the ideality factor decreases with light intensity. The obtained results indicate that GaAs/GO diode can be used as a photosensor in optoelectronic applications. Also, Schottky diode has been measured by capacitance-voltage (C-V) and conductance-voltage (G-V) in the frequency range from 10 kHz to 1 MHz at room temperature.
Keywords: Graphene Oxide; GaAs; Schottky Contacts; Current-Voltage; NEGATIVE CAPACITANCE; SERIES RESISTANCE; ELECTRONIC PARAMETERS; VOLTAGE-DEPENDENCE; V CHARACTERISTICS; INTERFACE STATES; C-V; FREQUENCY; TEMPERATURE; INTERLAYER; Engineering; Science & Technology - Other Topics; Physics